(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Four new Schiff bases were synthesized from condensation of aldehyde ( 2-hydroxy benzaldehyde ) with aromatic amines (4-introaniline ; 4,4-oxydianiline ; 4,4-diaminodipleny sulfone and sulfanilamide) . These Schiff bases were characterized by IR, NMR , GC. mass and element analysis. Moreover, the Schiff bases were screened for their antibacterial and antifungal activity against various microorganisms and compared with standard compounds. In general , the results were indicated that some Schiff bases had good antimicrobial activity.